2010
DOI: 10.3945/jn.109.116749
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Feeding Phase Shifts Clock Gene and Sodium Glucose Cotransporter 1 (SGLT1) Expression in Rats

Abstract: The intestine exhibits striking diurnal rhythmicity in glucose uptake, mediated by the sodium glucose cotransporter (SGLT1); however, regulatory pathways for these rhythms remain incompletely characterized. We hypothesized that SGLT1 rhythmicity is linked to the circadian clock. To investigate this, we examined rhythmicity of Sglt1 and individual clock genes in rats that consumed food ad libitum (AL). We further compared phase shifts of Sglt1 and clock genes in a second group of rats following restricted feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
3
26
0
1
Order By: Relevance
“…[26][27][28]53 On top of these long-term regulations, the amount of SGLT1 in the BBM of enterocytes is posttranscriptionally upregulated within minutes in response to high small intestine glucose concentrations. 21,54 In addition, it has to be considered that SGLT1 expression undergoes a diurnal rhythm in rodents [32][33][34][35] and that SGLT1 is expressed differentially in different small intestinal parts. 31,32 Considering this complex situation, we determined the concentrations of SGLT1 mRNA and SGLT1-mediated D-glucose uptake into enterocytes in different parts of the small intestine between 9 and 10 AM, using animals that had been starved for about 18 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28]53 On top of these long-term regulations, the amount of SGLT1 in the BBM of enterocytes is posttranscriptionally upregulated within minutes in response to high small intestine glucose concentrations. 21,54 In addition, it has to be considered that SGLT1 expression undergoes a diurnal rhythm in rodents [32][33][34][35] and that SGLT1 is expressed differentially in different small intestinal parts. 31,32 Considering this complex situation, we determined the concentrations of SGLT1 mRNA and SGLT1-mediated D-glucose uptake into enterocytes in different parts of the small intestine between 9 and 10 AM, using animals that had been starved for about 18 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the possibility that intestinal surgery influences SGLT1 expression was discussed. [32][33][34][35] To understand the mechanism of how DJB and RYGB affect diabetes type 2, it is necessary to know if SGLT1-mediated translocation of D-glucose and SGLT1-mediated glucose-dependent secretion of enterohormones change after these procedures. First results in nonobese, nondiabetic rodents showed a reduced SGLT1-mediated D-glucose translocation.…”
mentioning
confidence: 99%
“…Clock genes are expressed in all regions of the gut in rodents, from the stomach to the caecum and predominantly in enterocytes[50]. Clock , Bmal1 , Per1 , Per2 , Cry1 , Cry2 , ReverbA and ReverbB have all been found to exhibit diurnal rhythmicity in rodent jejunal mucosa[51] with a similar phase compared to the liver but a phase delay of approximately 6 hours compared to the SCN[41, 43, 52, 53]. Several studies have subsequently confirmed that the transcriptional rhythmicity of some of these genes is matched by rhythmicity in protein expression[45, 54, 55].…”
Section: The Circadian Clockworkmentioning
confidence: 99%
“…Several investigators have shown that these transporters show rhythmic expression with peak levels at night. Further, restricted feeding has been shown to shift the expression of these genes [13]. In contrast to wildtype mice, SGLT1, GLUT2 and GLUT5 mRNA did not show diurnal changes in Clock Δ19/Δ19 mice, suggesting that Clock plays a role in circadian regulation of these genes.…”
Section: Circadian Rhythms and Intestinementioning
confidence: 99%